Religion and Politics In China - Laurence T Murphy, (Journal of Dharma, 1982)
A traveller to China is struck by two things. its size and its antiquity. The sheer physical size of China is emphasized by the difficulty of travel to the interior regions. but the size of the population is immediately evident on the streets of the great cities. A billion people. nearly one quarter of the human race live in China. It is said that by the end of the century China will add the equivalent of the present population of the United States! As for its antiquity. it is reflected in China's historical treasures. its literature and its art. as even a casual tourist will note in the museums and countless other reminders of the past incorporated into cultural forms. Thus for more than 3.000 years China has developed its perspective on human life and its meaning. During much of this time the country has been divided into a small educated and well-to-do upper class of officials and scholars, and the masses of poor and illiterate peasants and menial workers. This division is reflected in Chinese religious traditions.